Intersectionality: A Means for Addressing the Needs of Children with Mental Health Issues who are Engaged with the Family Law and Criminal Justice Systems? - Bergman, Jennifer (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2019)
Huge numbers of children in Canada suffer from mental health issues, yet only a fraction gets needed supports and services.  Left untreated, childhood mental illnesses carry serious consequences for children, families, and society as a whole.  This public health crisis is significantly more pronounced for children who are engaged with the family law (child welfare) and youth criminal justice systems (“crossover youth”).  Crossover youth face multiplicative challenges, including disproportionate rates of mental health issues.  In this article, I explore how the failure to provide crossover youth with needed supports and services, and the related dire consequences suffered by these children and society more generally (e.g. deteriorating mental health, repeated engagement in the criminal justice system) is tied to the failure in the family law (child welfare) and youth criminal justice systems to recognize the effects of the intersection of the various challenges and disadvantages (e.g. poverty, racism, instability) experienced by these children. I describe the paradigm of intersectionality, and argue that the adoption of an intersectional approach by the family law (child welfare) and youth criminal justice systems is imperative in order for the legal system to meet its mandate and protect and promote the well-being of these vulnerable children.